28 MESENTERIC TERTIARY LYMPHOID ORGANS INTEGRATED INTO THE INTESTINAL-DRAINING LYMPHATIC NETWORK ARE RESISTENT TO ANTI-TNF THERAPHY IN CROHN'S DISEASE MOUSE MODEL. (7th February 2019) - Czepielewski, Rafael S; Kim, Ki-wook; Onufer, Emily J; Erlich, Emma; Williams, Jesse; Bala, Shashi; Saunders, Brian; Zinselmeyer, Bernd; Randolph, Gwendalyn J
Abstract: Characterization of Crohn's disease (CD) includes susceptible mucosal surfaces via abnormal intestinal permeability caused by either deregulated interactions between the bacterial flora and surface epithelial cells or an overwhelming host immune response. However, historical and recent studies demonstrate lymphatic vessel obstruction and lymphangitis as a critical component of CD. A hallmark of CD is lymphatic vessel swelling, poor drainage, with submucosal edema derived from the dysfunctional lymphatics. Given that lymph flow is essential for lipid absorption and antigen transport, we recently show obstructed mesenteric lymphatic drainage in CD patient biopsies through the development of tertiary lymphoid organs (TLO) on mesenteric collecting vessels. However, this feature of the disease is unknown in inflammatory bowel disease (IBD) mice models. We sought to investigate intestine-draining lymphatics in IBD using whole-mount image and confocal microscopy. We define the existence of TLO associated with mesenteric lymphatic vessels in a well-establish mouse model of chronic ileitis (TNF ΔARE model). We generated an inducible lymphatic endothelial cell reporter (Prox1creER-tdTomato) containing TNF ΔARE deletion, which develops ileitis. These allow us to confirm mesenteric lymphangiogenesis and association with TLO in the obstruction of intestinal draining lymphatic collectors in mice. Surprisingly, anti-TNF treatment of TNF ΔARE mice fails to regress established mesenteric TLO. We investigate lipid and immune cell trafficking using photoactivatable systems to investigate lymphatic network remodeling during IBD progression. These findings suggest that chronic inflammatory imbalance promotes lymphatic remodeling and TLO formation outside the intestine. Our future directions focus on whether tertiary lymphoid tissues prevent dendritic cell migration and their upstream tolerogenic control.